Conflits d’aménagement, mobilisations territoriales et jeux institutionnels local Région État en Italie : le projet d’agrandissement de l’aéroport de Rome-Fiumicino - Dominique Rivière (L'Espace Politique)
Local planning conflicts bring a new perspective to territorial public action. The paper explores the Italian case and more specifically the planning conflict generated by the Fiumicino Airport expansion project, and is focused on the role of institutional scale articulations between local/regional/national levels in the dynamics of these conflicts. Beyond the diffusion of the territorial conflicts in Italy, this example highlights the ambiguous role of the local level in its relationships with the other levels (the Region and more especially the State). The local level is both a central one, for its proximity with the mobilization of the residents, and a weak one, confronted to the return of the State to the front of the stage. Local mobilizations, using complex and contradictory institutional temporalities, appear to be an opportunity for a resourcing of the territorial public action and have contributed to the evolution of the infrastructure project.